Using the pluriverse concept to critique Eurocentrism in education (Journal of Applied Learning and Teaching, 2020)
It is widely acknowledged that teachers need to interrogate and transform how Eurocentrism underpins educational practice. This paper argues that teachers can actively engage with decolonial frameworks and concepts to productively expose how Eurocentric categories of thought shape teaching practice and curriculum. We describe how six teachers “walked with” the decolonial concept of the pluriverse (a sense of multiple coexisting differences) during collaborative reflections about our diversity teaching of culturally safe healthcare. Our research processes drew on the principles of collaborative, reflective practice. We co-participated in conversations, which aimed to collectively explore how the pluriverse concept intersected with our teaching and undertook qualitative coanalysis of themes emerging across these dialogues. The paper outlines how employing the pluriverse concept as a companion to our reflective process enabled us to ask critical questions about Eurocentrism in our teaching practice and content. Our questioning, in turn, generated principles for embedding the pluriverse in the curriculum, pedagogical approaches, and teacher dispositions. The paper discusses what enables and hinders the pluriverse being embedded in curriculum materials and classroom activities and the limitations of our activities in relation to the broader project of decolonising pedagogy.